Exploring Electronic and Structural Properties of Titanium-Doped Chlorapatite: A Theoretical and Experimental Investigation - Keser, Serhat; Ateş, Tankut; Bulut, Niyazi; Kaygılı, Omer (Niyazi BULUT, 2023)
The apatite family stands as a pivotal class of inorganic compounds with diverse elemental components, playing a crucial role in biological, environmental, and geological contexts. Among these, chlorapatite (ClAp) emerges as a significant member, featuring a hexagonal structure with the space group P63/m. In this theoretical study, we delve into the unexplored realm of Ti-doped ClAp structures, investigating their electronic and structural characteristics for the first time. Motivated by the potential impact of titanium (Ti) doping on electronic and optical properties, we employ density functional theory (DFT) principles to perform band structure calculations. The electronic band structure is explored comprehensively, shedding light on the energy distribution for electrons as a function of momentum. Our calculations reveal that un-doped ClAp exhibits an insulating nature, as indicated by a calculated band gap of approximately 4.947 eV. The theoretical volume parameter closely matches experimental observations, validating the reliability of our computational model. Introducing Ti as a dopant in 1.2TiClAp results in a discernible increase in the band gap to approximately 5.339 eV. The theoretical volume parameter exhibits excellent agreement with experimental data, emphasizing the precision of our calculations. For 2.4TiClAp, the band gap remains stable at around 5.344 eV, while the theoretical volume parameter stands at 0.5260 nm3. Our systematic exploration of Ti-doped ClAp underscores the tunability of electronic properties, signifying potential applications across diverse fields. The reliability of theoretical calculations is further affirmed by the consistent alignment with experimental parameters. These findings contribute significantly to our fundamental understanding of Ti-doped ClAp, providing crucial insights for material design and optimization. Ongoing collaborative efforts between theoretical and experimental approaches are essential for a comprehensive assessment of these complex materials.
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri